Synthesis and characterization of Co-5Cr-RHA hybrid composite using Powder metallurgy. (2021) - Arunachalam, U.; Raghav, G.R.; Dhanesh, S.
Abstract: Cobalt-Chromium alloys are in high demand as a material for prosthetics and dental implants. Powder metallurgy was used to create Co-5Cr-RHA (Rice Husk Ash) hybrid composites in this research. RHA is made by heating rice husk in a furnace to 700 degrees Celsius. The surface morphology of the Co-5Cr-RHA hybrid composites is analysed using a scanning electron microscope. Due to the RHA reinforcement, the Micro hardness of the Co-5Cr-10RHA hybrid composite increased by 8% as compared to other samples. The density of the hybrid composites has decreased as a result of the addition of RNA. The compressive strength of the Co-5Cr-10RHA (130 MPa) hybrid composites has increased by 4%. The addition of RNA reinforcement has a positive effect on tribological behaviour, according to tribological studies. Because of the oxides in the RHA, wear loss and COF have decreased significantly. The after-wear SEM analysis confirms that abrasive wear is the primary wear mechanism. The corrosion behaviour of the Co-5Cr-RHA hybrid composites was investigated using the electrochemical workstation in the presence of a 3 percent NaCl electrolytic solution. Of all specimens, Co-5Cr-10RHA hybrid composites have a stronger Ecorr value of −0.812 V.